IoT and Competitive Advantage: A Bibliometric Analysis of Digital Business Strategy - Loso Judijanto (Westscience Press, 2025)
This study provides a comprehensive bibliometric analysis of scholarly research examining the relationship between the Internet of Things (IoT) and competitive advantage within the context of digital business strategy. Drawing on publications indexed in the Scopus database from 2010 to 2025, the study applies bibliometric techniques using VOSviewer to map the intellectual structure, thematic evolution, and collaboration patterns in this rapidly growing research domain. The analysis includes keyword co-occurrence, co-citation, co-authorship, and country-level collaboration networks to identify dominant research themes, influential contributions, and emerging trends. The findings reveal that digital transformation, competition, and business strategy constitute the core conceptual anchors of IoT-related research, indicating that IoT is increasingly framed as a strategic capability rather than a purely technological tool. Enabling technologies such as artificial intelligence, data analytics, cloud computing, and blockchain are shown to play a critical role in reinforcing IoT-driven competitive advantage. In addition, emerging themes related to sustainability and cybersecurity highlight a shift toward more holistic and responsible digital business strategies. This study contributes to the literature by synthesizing fragmented research streams and offering a structured overview of how IoT supports strategic value creation. The results provide valuable insights for academics and practitioners seeking to understand the strategic implications of IoT adoption in an increasingly digital and competitive business environment.⁠